ANALISA PENGARUH CURRENT RATIO (CR), NET PROFIT MARGIN (NPM), DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PT. JAPFA COMFEED INDONESIA Tbk PERIODE 2014 – 2020 PER KUARTAL - Dandono, Yustinus Rawi; Jesslyne, Jesslyne (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2023)
ABSTRACT This study aims to determine and analyze (1) the effect of Current Ratio (CR) on Stock Prices, (2) the effect of Net Profit Margin (NPM) on Stock Prices, (3) the effect of Debt to Equity Ratio (DER) on Stock Prices, ( 4) the effect of Earning Per Share (EPS) on Stock Prices, (5) the effect of Current Ratio (CR), Net Profit Margin (NPM), Debt to Equity Ratio (DER) and Earning Per Share (EPS) on Stock Prices. The data used in this study were obtained from the quarterly Published Financial Reports of PT. Japfa Comfeed Indonesia Tbk period 2014 – 2020. The results showed that partially the DER variable has a significant effect on stock prices. While the CR, NPM and EPS variables have no significant effect on stock prices. Simultaneously the variables CR, NPM, DER, and EPS affect stock prices. The adjusted R-squared value in this study is 0.478, which means that the ability of the independent variable to explain the variation in the dependent variable is 47.8%, while the remaining 52.2% is explained by other independent variables outside the model.